The structure of variability in shoot and fruit traits of subalpine populations of Fagus orientalis Lipsky in the Western and Eastern Caucasus - Kh. U. Aliev (Юг России: экология, развитие, 2024)
Aim. Comparative study and analysis of the variability of characters of the shoots and fruit of Fagus orientalis Lipsky from subalpine populations of the Western and Eastern Caucasus.   Material and Methods. For the analysis randomly collected annual shoots with fruit from 47 Fagus orientalis trees from 6 populations of the Western and Eastern Caucasus were used. Measurement data from 12 traits were used to identify variability. The total repetition of measurements for each trait for 6 populations was 1318.   Results. A comparative study of the variability of traits in the shoot and fruit of Fagus orientalis from 6 populations of the Eastern and Western Caucasus showed a predominance of size traits in individuals from the Eastern Caucasus. The trait “length of annual shoot” had the highest level of variability – 70.6 %. Low and medium levels were detected in fruit traits, leaf blade length and width, and plus length. The results of Student's t‐tests showed the greatest significance of differences in the “length of annual bud” trait – 28.98. Correlation analysis revealed positive, reliable relationships for most pairs of characteristics. The closest of them are noted in all fruit characters and in the character of length and width of the leaf blade.   Conclusions. The predominance of size values of traits in individuals from populations of the Eastern Caucasus is associated with climatic conditions – the growing season in the Western Caucasus being shorter by almost a month. The low level of variability of fetal traits confirms their high genetic determination. The “apical bud length” trait can be used as an indicator, reflecting the degree of influence of environmental factors on populations. The closest correlations are manifested by the characteristics of the fruit and a pair of characteristics ‐ the length and width of the leaf blade.